Phytochemical and in vitro antidiabetic investigations of stems of Tetracera Indica Merr., a Malaysian traditional medicinal plant - Hasan, Md. Mahmudul (Stu); Mat So'ad, Siti Zaiton; Shafiq, Tengku Muhammad Faris; Bakhtiar, M. Taher; Latip, Jalifah; Ahmad, Farediah; Sarian, Murni Nazira; Tunna, Tasnuva Sarwar; Ahmed, Qamar Uddin (2015)
Tetracera indica Merr. (Family: DILLENIACEAE) is a large, woody, rain forest climber of Malaysia which is commonly known as Mempelas paya or sand paper plant. Different parts of T. indica are traditionally used to treat various ailments including diabetes. Four flavonoids (MHQ1-Wogonin, MHQ2-Norwogonin, MHQ3-Quercetin, MHQ4-Techtochrysin) and two terpenoids (MHQ5-Stigmasterol, MHQ6-Betulinic acid) were isolated from the stems ethanol extract of T. indica and subjected to cytotoxicity test against 3T3-L1 adipocytes with regard to evaluate their antidiabetic potential. All the compounds were isolated and purified through silica gel and sephadex LH-20 column chromatography and recrystallization with ethanol and their structures were elucidated through 1D and 2D 1H- and 13C-NMR spectroscopy and their spectral data were compared with the previously reported data of the same compounds. Cytotoxicity test was performed by MTT assay on 3T3-L1 pre-adipocytes to determine the safe dose of all isolated compounds. MHQ1 and MHQ4 showed IC50 below 100 µg/ml whereas rest of the compounds found to be safe up to 100 µg/ml. MHQ1, MHQ2, MHQ3 and MHQ4 were further subjected to adipogenesis to investigate insulin like activity or insulin sensitizing activity for the purpose of evaluating antidiabetic activity. All compounds were introduced to the cells in different safe concentrations as well as in different adipogenic cocktails. The adipogenic cocktails were modified by the compounds and rosiglitazone in the presence or absence of insulin. Results showed that MHQ-1, MHQ-2 and MHQ-4 induced adipogenesis like insulin and enhanced adipogenesis like rosiglitazone significantly. Furthermore, MHQ1 and MHQ2 as well as rosiglitazone as positive control were subjected to fluorescence glucose uptake test by 2-NBDG (fluorescent glucose analog) on mature adipocytes. Results suggested significant glucose uptake activity by MHQ1 and MHQ2. It is suggested that further study on the isolated compounds might help to discover a new safe compound with strong antidiabetic activity.